Social Determinants of Health Associated with Cholangiocarcinoma Risk in High-Risk Areas of Thailand: A Case-Control Study - Khuanthong, Pranom; Songserm, Nopparat; Thongchai, Comsun; Chada, Wilawun (Asian Pacific journal of cancer prevention : APJCP, 2024)
This case-control study sought to explore the social determinants of health (SDH) associated with cholangiocarcinoma (CCA) risk in high-incidence regions of Thailand. The research was conducted in two phases. Phase 1 assessed the prevalence, context, and conditions among at-risk populations for CCA in Yasothon, located in Northeast Thailand. This phase utilized a survey-based research design, employing verbal screening methods to categorize individuals into risk groups (at-risk vs. not at-risk). Phase 2 aimed to identify the SDH associated with CCA risk through a case-control study. Of 496 recruited participants, 238 cases of subjects were at risk of CCA, and 258 controls were not at risk of CCA. Data were collected using structured questionnaires. Multiple logistic regression was employed to analyze the factors associated with CCA risk. The study revealed that 48.00% of participants were at risk for CCA, with 32.06% having a history of liver fluke eggs detected in their feces. Despite this, only 45.40% of participants engaged in adequate preventive behaviors. Analysis of SDH among the cases identified significant challenges, including high levels of poverty (49.14%), food security (52.22%), social exclusion (48.82%), inadequate housing (50.22%), and overall SDH burden (53.42%). In contrast, relatively lower levels of health inequality (48.78%) and unfavorable working conditions (51.65%) were observed. Multivariate analysis indicated that overall SDH was a significant risk factor for CCA (AOR=1.63; 95% CI: 1.09-2.46), while perceived disease severity (AOR=0.57; 95% CI: 0.39-0.83) and safe working conditions (AOR=0.61; 95% CI: 0.42-0.90) were protective factors. Improving CCA prevention behaviors should focus on enhancing perceived severity and addressing the relevant SDH.